2019
DOI: 10.3847/1538-4357/aaf16f
|View full text |Cite
|
Sign up to set email alerts
|

Observations of an Electron Diffusion Region in Symmetric Reconnection with Weak Guide Field

Abstract: The Magnetospheric Multiscale spacecraft encountered an electron diffusion region (EDR) in a symmetric reconnection in the Earth’s magnetotail. The EDR contained a guide field of about 2 nT, which was 13% of the magnetic field in the inflow region, and its thickness was about 2 local electron inertial lengths. Intense energy dissipation, a super-Alfvénic electron jet, electron nongyrotropy, and crescent-shaped electron velocity distributions were observed in association with this EDR. These features are simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
121
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 93 publications
(136 citation statements)
references
References 45 publications
14
121
1
Order By: Relevance
“…Similar temperature anisotropy and bidirectional electron velocity distributions have been found in the inflow region of the diffusion region (Chen et al, 2009; Huang et al, ; Zhou et al, ). It is suggested that acceleration by parallel electric field causes the temperature anisotropy in the inflow region (Egedal et al, ).…”
Section: Novel Properties Of the Idrsupporting
confidence: 65%
See 2 more Smart Citations
“…Similar temperature anisotropy and bidirectional electron velocity distributions have been found in the inflow region of the diffusion region (Chen et al, 2009; Huang et al, ; Zhou et al, ). It is suggested that acceleration by parallel electric field causes the temperature anisotropy in the inflow region (Egedal et al, ).…”
Section: Novel Properties Of the Idrsupporting
confidence: 65%
“…MMS observed an EDR in the magnetotail on 10 August 2017 (Zhou et al, ). This EDR was embedded within a much larger IDR.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Here we will present only the data relevant to our analysis. For more details about this event, see the description of Zhou et al ().…”
Section: Resultsmentioning
confidence: 99%
“…The EDR had been difficult to identify mainly because of its small size in conjunction with the limited ©2019. Another magnetotail EDR event reported by Zhou et al (2019) also exhibited J▪E′ > 0, electron agyrotropy, and super-Alfvénic electron jets. This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.…”
Section: Introductionmentioning
confidence: 83%